2009
DOI: 10.1007/s12245-009-0091-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the point-of-care blood gas analyzer versus the laboratory auto-analyzer for the measurement of electrolytes

Abstract: BackgroundElectrolyte values are measured both by arterial blood gas (ABG) analyzers and central laboratory auto-analyzers (AA), but a significant time gap exists between the availability of both these results, with the ABG giving faster results than the AA. The authors hypothesized that there is no difference between the results obtained after measurement of electrolytes by the blood gas and auto-analyzers.MethodsAfter approval by the ethics committee, an observational cohort study was conducted in which 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 13 publications
7
91
0
2
Order By: Relevance
“…According to Jain A et al, the cause for lower values of electrolytes in arterial blood is because of binding of heparin to electrolytes [11]. R King et al, observed that there was good agreement between the sodium and potassium values measured by ABG analyser and chemistry autoanalyser [12].…”
Section: Resultsmentioning
confidence: 99%
“…According to Jain A et al, the cause for lower values of electrolytes in arterial blood is because of binding of heparin to electrolytes [11]. R King et al, observed that there was good agreement between the sodium and potassium values measured by ABG analyser and chemistry autoanalyser [12].…”
Section: Resultsmentioning
confidence: 99%
“…electrolyte analyzer with Indirect ISE i.e. auto analyzer where some studies have shown no similarity between parameters and some showed similarity with potassium but not for other [10] as both principles employed in analysis for electrolyte measurement were different so results in each study differed. But in our study we have observed that there are significant differences in the values in all the ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmamızda iki metot arasındaki fark daha önce bildirilen arter kan gazı ile laboratuvar potasyum sonuçlarını karşılaştıran çalışma-lardaki farktan daha yüksektir (4)(5)(6)(7)9). Bu çalışmaların ikisinde bizim çalışmamızdan farklı olarak arter kan gazı ortalama potasyum değer-leri laboratuvar potasyum değerlerinden daha yüksek bulunmuştur.…”
Section: Discussionunclassified